From Rare Gas Atoms to Fullerenes: Spherical Aromaticity Studied from the Point of View of Atomic Structure Theory - Reiher, Markus; Hirsch, Andreas (Chemistry - A European Journal, 2003)
The characteristic features of molecules like polyhedra and fullerenes, which follow the 2(N+1) rule of spherical aromaticity, can be related to energetically stable closed-shell configurations of (pseudo-)atoms. This unifying view relies on a thought experiment, which produces a polyhedron in a two-step process and which can, in turn, relate the electronic configuration of any spherical polyhedron to the one of a corresponding closed-shell atom. In the first step, the electronic ground-state configuration is identified. In the second step, a group theoretical analysis can be carried out; this relates the spherically symmetric atomic orbitals to the molecular orbitals classified according to the irreducible representations of the point group of the polyhedron under consideration. This procedure explains and justifies the pseudo-l classification of molecular orbitals, which is the basis of the 2(N+1) rule. For the transition from the electronic configuration of the rare gas Eka-Rn (Uuo) to the icosahedral fullerene C , we show how a change in the ground-state configuration leads to the phenomenologically found 2(N+1) rule for spherically aromatic fullerenes.